Universal off-the-shelf combination immunotherapy using oncolytic viruses to redirect T cell engagers to target solid tumors - Stephen J Forman; Wen-Chung Chang; Xiuli Wang; Anthony K Park; Ryan Urak; Yuman Fong; Monil Shah; Colin Cook; Yukiko Yamaguchi; Saul J Priceman; Cathy Lu; Shyambabu Chaurasiya; et al. (Journal for ImmunoTherapy of Cancer)
Background Bispecific T cell engager (BiTE), such as blinatumomab, has demonstrated significant clinical success in treating hematological malignancies like B cell acute lymphoblastic leukemia and non-Hodgkin's lymphoma. However, the application of BiTEs in solid tumors has proven challenging, primarily due to the lack of targetable tumor antigens and the immunologically “cold” nature of the tumor microenvironment, which limits immune system activation.Methods We developed a novel oncolytic virus (OV) platform by engineering a chimeric vaccinia virus to express either a truncated non-signaling CD19 antigen (CD19t) or truncated B cell maturation antigen (BCMAt) on the surface of infected tumor cells. Here, we advance a combinatorial platform using an OV to redirect CD19-targeted or BCMA-targeted T cell engagers (TCEs) to drive antitumor responses against multiple solid tumors.Results We found that OV-infected tumor cells in combination with TCEs significantly improved tumor cell killing against solid tumor models, with efficacy comparable to that of chimeric antigen receptor T cells. This combination approach enhanced antitumor responses using in vivo human tumor xenograft models and promoted more effective elimination of solid tumor cells than either therapy alone. Our studies highlight OVs combined with clinically approved TCEs as a readily translatable, tumor-agnostic, off-the-shelf strategy to effectively target solid tumors.Conclusions Our findings demonstrate that the combination of OV and TCEs offers a promising strategy to drive antitumor immune responses against solid tumors. This approach represents a novel and universal platform currently in phase 1 clinical trial combining TCE therapy with oncolytic virotherapy, overcoming antigen heterogeneity and immunological barriers for the effective treatment of solid tumors.